Business strategy and performance of Algerian exporting SMEs - Besten, Mohamed El Amine (2017)
Despite the importance of business strategy to small and medium-sized enterprises (SMEs), the literature reveals that there are limited studies that have attempted to investigate business strategy and organizational performance among the exporting SMEs in Algeria. This has resulted in little information and knowledge about the relationship between business strategy and the performance SMEs in Algeria. Given this, this study initiates an attempt to examine the linkage between six types of business strategy and organizational performance of exporting SMEs in Algeria. By using structured questionnaire, the data for the study was collected from exporting 72 SMEs located in the northern region of Algeria. The correlation analysis was used to test the hypotheses developed in the study. The results of the study show that the six types of business strategy are significantly associated to the performance of the exporting SMEs as measured in terms of sales, net profit, number of employees and number of products.